Low Levels of MicroRNA-10a in Cardiovascular Endothelium and Blood Serum Are Related to Human Atherosclerotic Disease. (15th July 2021) - Kuo, Jong-Tar; Tsai, Hsiao-En; Lin, Ching-Ting; Lee, Chih-I; Lee, Pei-Ling; Ruan, Yu-Rong; Chiu, Jeng-Jiann; Lee, Ding-Yu
Abstract : Background . MicroRNA-10a (miR-10a) inhibits transcriptional factor GATA6 to repress inflammatory GATA6/VCAM-1 signaling, which is regulated by blood flow to affect endothelial function/dysfunction. This study aimed to identify the expression patterns of miR-10a/GATA6/VCAM-1 in vivo and study their implications in the pathophysiology of human coronary artery disease (CAD), i.e., atherosclerosis. Methods . Human atherosclerotic coronary arteries and nondiseased arteries were used to detect the expressions of miR-10a/GATA6/VCAM-1 in pathogenic vs . normal conditions. In addition, sera from CAD patients and healthy subjects were collected to detect the level of circulating miR-10a. Results . The comparison of human atherosclerotic coronary arteries with nondiseased arteries demonstrated that lower levels of endothelial miR-10a are related to human atherogenesis. Moreover, GATA6/VCAM-1 (a downstream target of miR-10a) was highly expressed in the endothelium, accompanied by the reduced levels of miR-10a during the development of human atherosclerosis. In addition, CAD patients had a significantly lower concentration of miR-10a in their serum compared to healthy subjects. Conclusions . Our findings suggest that low miR-10a and high GATA6/VCAM-1 in the cardiovascular endothelium correlates to the development of human atherosclerotic lesions, suggesting that miR-10a signaling has the potential to be developed as a biomarker for human atherosclerosis.